Тіларалық баламалардың мәдени және ұлттық ұқсастықтары мен айырмашылықтары - M., Grein; G., Kapysheva; S., Beissenova (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2021)
Culture as a complex concept, which lies in the sphere of interests of almost all humanities, is of particular interest in the linguistic context. Language is a tool of communication pattern, which expresses the cultural mentality of the people. Citing the German philosopher R. Konesmann, Kusse H., Chernyavskaya V. E. believes that the discourse of culture is language, based on various areas of communication. Language, as well as culture, is a complex phenomenon that represents a semantic concept in all spheres of human life, reflects cultural characteristics and reveals the rich cultural experience of individual peoples. In this regard, the linguist analysis of multi-system languages is interesting. The purpose of this article is a comparative study of multi-system languages in a practical and theoretical way. The paper presents different languages comparative study, contrastive research has a theoretical applied and practical significance. Forms of knowledge about the world have been presented in the concept of «measurement» in different structural languages. One of the tasks of contrastive researches is to reveal the cultural and national similarities and differences of the inner form interlanguage equivalents. The facts of cultural and national similarities and differences of two or more languages in order to detect convergence and discrepancy are very popular from the point of linguistic universals. Key words: culture, communication, linguistics, interlingual equivalents, idioms.